Congenital Descending Colonic Stenosis with Perforation of Transverse Colon in a Neonate: A Case Report - Hamid, R; Shera, AH; Bhat, NA; Baba, A; Rashid, A (Journal of Nepal Paediatric Society, 2012)
Colonic atresia and stenosis are rare causes of intestinal obstruction in the infant. Only 10 cases have been reported in Literature since 1966 and only one late-onset case has been reported in Literature until now. We describe the case of a 3 day old baby presenting with abdominal distension, failure to pass meconium and vomiting. X-ray of the abdomen showed dilated gut loops. Exploratory laparotomy was performed. At the junction of descending and sigmoid colon a stenosis was found, laparotomy also revealed a perforation of transverse colon. Transverse colostomy and a mucous fistula of sigmoid colon was performed after resecting stenosing segment and colon distal to perforation site upto stenosing site. Diagnosis was confirmed on histopathology. Colostomy was close after six weaks with uneventful recovery. Considering both the Literature and our case, congenital colonic stenosis should be considered one of the rare differential diagnoses in a neonate presenting as complete or partial intestinal obstruction. Key words: Colonic Stenosis; Perforation; Obstruction DOI: http://dx.doi.org/10.3126/jnps.v32i1.5446 J. Nepal Paediatr. Soc. Vol.32(1) 2012 73-75